شركات التكنولوجيا المالية الخضراء كتوجه جديد لتمويل الاستثمارات الصديقة للبيئة -دراسة حالة الشركة الأمريكية Stripe Climate- - دراجي أسماء; دحماني نور الهدى (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة الى تسليط الضوء على أهم التوجهات الحديثة في عالم المال والأعمال وهي ما تعرف بشركات التكنولوجيا المالية الخضراء التي انتهجت ممارسات صديقة للبيئة حيث تعمل على توفير العديد من الخدمات الخضراء إضافة الى تمويلها لمختلف أنواع الاستثمارات الصديقة للبيئة، بهدف تحقيق أبعاد التنمية المستدامة الاقتصادية، البيئية والاجتماعية، وذلك من خلال تشخيص وتحليل تجربة شركة التكنولوجيا المالية الخضراء stripe climate في تمويل الاستثمارات الخضراء لمحاربة التغيرات المناخية عن طريق العديد من المشاريع في مختلف دول العالم التي تستخدم أحدث التقنيات التكنولوجية في التقاط ثاني أكسيد الكربون، وقد خلصت الدراسة الى أهمية تبني التمويل الأخضر ودعم الاستثمارات الصديقة للبيئة من طرف شركات التكنولوجيا المالية، حيث يساهم ذلك في التقليل من البصمة الكربونية والحفاظ على النظم البيئية الى جانب الدفع بالتنمية الاقتصادية. This study aims to highlight the importance of recent trends in the world of finance and business, known as green fintech companies. These companies have adopted environmentally friendly practices, offering a variety of green services in addition to financing various types of green investments. The goal is to achieve economic, environmental, and social dimensions of sustainable development by diagnosing and analyzing the experience of the green fintech company Stripe Climate in financing green investments to combat climate change through various projects worldwide that utilize cutting-edge technological solutions for carbon capture. The study concludes on the importance of embracing green finance and supporting environmentally friendly investments by fintech companies, as this contributes to reducing carbon footprint and preserving ecosystems while promoting economic development
Green fintech companies as a new trend for financing green eco-friendly investments -Case study of the American company Stripe Climate
Keywords: شركات التكنولوجيا المالية الخضراء; التنمية المستدامة; التمويل الأخضر; الاستثمارات الصديقة للبيئة; eco-friendly investment; green financ; sustainable developmen; green fintec; companie; Stripe Climate compan